Quantification of physiological, movement, and technical outputs during a novel small-sided game in young team sport athletes - Harrison, C. B.; Gill, N. D.; Kinugasa, T.; Kilding, A. E. (The Journal of Strength and Conditioning Research, 2013)
The aim of this study was to quantify the physiological responses, time-motion characteristics, and technical executions associated with a novel non-sport-specific small-sided game (SSG) in young team sport players. On 6 separate occasions, 12 young male team sport athletes (mean ± SD: age, 13.0 ± 0.3 years; height, 157.4 ± 4.9 cm; body mass, 47.0 ± 5.0 kg; and VO2peak, 55.1 ± 4.6 ml/kg/min) completed various "bucketball" SSG formats (i.e., 3 vs. 3, 4 vs. 4, and 6 vs. 6) twice each. Heart rate (HR) was measured during each SSG at 5-second intervals. Time-motion characteristics were measured using global positioning systems. Ratings of perceived exertion (RPEs) were recorded immediately after the SSGs using the Borg scale (RPEs, 6-20). Technical skill executions were measured using a high-speed digital video camera. Analysis revealed a tendency for the 3 vs. 3 games to elicit higher HRs (88.3 ± 4.3) than either 4 vs. 4 (85.9 ± 4.9) or 6 vs. 6 formats (85.9 ± 3.2). Total distance traveled at 13-17.9 km/h was more during 6 vs. 6 than 3 vs. 3 games (very likely substantial true difference, 97%), and total possessions and number of catches, passes, and shots were all higher in 3 vs. 3 compared with 4 vs. 4 and 6 vs. 6 games. There was no difference in RPE between the game formats. The results of this study indicate that 3 vs. 3 non-sport-specific SSGs provide higher stimulus for aerobic fitness adaptation and technical improvement than 4 vs. 4 and 6 vs. 6 formats, and their use for training young team sport athletes is recommended.